Development of digital literacy model for college students in Minzu colleges and universities in Southwest China - Wang, Jie; Boonphadung, Suttipong (Edelweiss Applied Science and Technology, 2024)
Constructing a digital literacy model for college students in Minzu Colleges and Universities in Southwest China is crucial for advancing the implementation of the "Action Plan for Improving National Digital Literacy and Skills" and effectively conducting digital literacy education. By researching digital literacy models from abroad and employing bibliometric methods, an initial conceptual framework for the digital literacy model for college students was developed. A mixed-methods research approach, combining quantitative and qualitative research, was used. Confirmatory Factor Analysis (CFA) was employed to test the validity and reliability of the initial model, which was then refined based on CFA results and expert feedback. In-depth interviews with experts were conducted to further optimize the model. The resulting digital literacy model for college students in Minzu Colleges and Universities in Southwest China not only holds significant implications for digital literacy education in this region but also provides a reference for constructing digital literacy models for other educational stages and in different regions. This model-building approach can serve as a valuable reference for similar research and practice.